Plant-based diets and sports performance: a clinical review - Maier II, S. P.; Lightsey IV, H. M.; Galetta, M. D.; Usoro, A. O.; Oh, L. S. (Sport Sciences for Health, 2023)
Purpose Plant-based diets have become increasingly popular in Western culture. Although studies have examined physiologic health improvements of plant-based diets, there is little data on plant-based diets as it relates to sports performance.